Energy conservation strategies on academic buildings using interpretive structural modeling to develop energy sustainability - Arbi, Yaumal; Frinaldi, Aldri; Rembrandt, Rembrandt; Lanin, Dasman; Umar, Genius (Universitas Negeri Padang, 2024)
Effective energy conservation strategies are required to be implemented in academic buildings as they consume significant energy while considering the convenience and function of the buildings. However, the influencing factors are interrelated and complex, requiring an appropriate approach to unravel the complexity. Therefore, this study aims to identify, analyse, and map the interaction relationship between factors affecting energy conservation in academic buildings. This study used Interpretive Structural Modeling (ISM) procedure starting from developing the Structural Self Interaction Matrix (SSIM), converting SSIM into a Reachability Matrix, revising the matrix, and categorizing the factors by using MICMAC analysis. This study involved 9 factors, including architectural design, illumination technology, education and awareness, energy monitoring and management, renewable energy use, efficient HVAC system, energy-saving equipment, institutional policies, and campus community participation. The study found that renewable energy use at level 3 was the factor that was not influenced by and did not interact with any other factors. Meanwhile, the illumination technology was a factor that interacted with the efficient HVAC System factor which was at level 1 where these two factors were influenced by other seven factors. This study aligns with current developments in energy conservation, including an increased focus on renewable energy and energy efficiency in academic buildings, supported by global and national policies aimed at achieving sustainability goals. It provides a comprehensive understanding on developing sustainable energy conservation strategies in academic buildings.